Bluebeard’s Castle by Béla Bartók. A reading hypothesis (Itinera, 2018)
Bluebeard’s Castle (A kékszakállú herceg vára), composed by Béla Bartók on a libretto by Béla Balázs, is one of the most significant musical works of the early twentieth century and a masterpiece of Hungarian modernism. The opera deals with “the eternal tragedy of the dualism between man and woman” from an original point of view, divergent from the widespread one in Western European thought and art. The essay investigates Bartók’s musical dramaturgy according to this topic.